B2B Platform for Education Centre integration - Ajanovski, Vangel; Kon-Popovska, Margita; Mishev, Anastas (Institute of Informatics, Faculty of Natural Sciences and Mathematics, Ss. Cyril and Methodius University in Skopje, Macedonia, 2002)
As the volume of B2B (Business-to-Business) transactions done over the Internet steadily increases, pressure is put on the companies to adopt themselves to the new way of trading. Such a case can also be seen at educational institutions. We propose a specialized B2B platform for integration of educational centers – an educational marketplace. This platform tries to provide a media for integration of all educational information produced by not just universities, but also other institutions. For that reason, the platform maintains a global catalogue of course descriptions, academics and resources and also unified access point for the virtual digital libraries and course contents, with unified information delivery - anytime and anywhere.
Keywords: virtual university, digital libraries, marketplace, peer-to-peer, P2P